Ru(II) complexes containing NOO donors of tridentate Schiff base ligands: Synthesis, characterization, crystal structure and catalytic activity in transfer hydrogenation of ketones - Premkumar Muniyappan; Vijayan Paranthaman; Venkatachalam Galmari (Chemistry of Inorganic Materials, 2023)
A new series of pincer type ruthenium(II) Schiff base complexes namely [Ru(CO)(PPh3)2(L1‒6)] (1–6) (where, L1‒6 ​= ​NOO ‒ donors of tri-dentate ligands) have been synthesized from ruthenium precursor such as [RuHCl(CO)(PPh3)3] containing tri-dentate Schiff bases ligands (H2L1‒H2L6). These ruthenium complexes were analyzed by elemental analysis and diverse characterizations such as FT‒IR, UV–Vis and NMR (1H and 31P) spectroscopy studies. The crystal structure of one of the complexes 5 ([Ru(CO)(PPh3)2L5]) was determined by single crystal X‒ray crystallography that revealed pincer type of coordination mode of complexes. Furthermore, complexes 1–6 have been utilized for transfer hydrogenation of aromatic ketones to secondary alcohols in the presence of i‒PrOH/KOH. The catalytic efficiency of complexes showed an efficient for transfer hydrogenation of ketones with alcohol as moderate to high conversions.